Aku adalah Pintu (Yohanes 10:7-9): Kajian Eksegesis dan Teologi Pastoral - Rumsory, Yoseph Mario (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
Jesus’ declaration “I am the gate” in John 10:7-9 is a rich theological metaphor that holds significant meaning for both Christological reflection and contemporary pastoral ministry. This article aims to examine the meaning of this statement through a biblical exegetical approach and pastoral theology. The research employs a qualitative method based on literary analysis, including a study of the Greek text and a contextual reading of the Gospel of John. The findings indicate that the metaphor of the “gate” emphasizes Jesus’ identity as the sole way to salvation and as the source of abundant life for believers. Moreover, this image highlights Christ’s pastoral function in granting access to a living relationship between God and humanity while providing protection and guidance for His flock. The pastoral implications of this text invite church ministers to imitate Christ as the gate by fostering openness, offering spiritual security, and promoting a liberating form of pastoral care. Thus, John 10:7–9 not only conveys profound theological insights but also offers a relevant pastoral paradigm for the Church’s mission in the contemporary context.